Multiparametric characterization of response to anti‐angiogenic therapy using USPIO contrast‐enhanced MRI in combination with dynamic contrast‐enhanced MRI. Issue 6 (4th December 2017) - Kim, Jana; Kim, Eugene; Euceda, Leslie R.; Meyer, Dan E.; Langseth, Karina; Bathen, Tone F.; Moestue, Siver A.; Huuse, Else Marie
Abstract : Background: Steady state susceptibility contrast (SSC)‐MRI provides information on vascular morphology but is a rarely used method. Purpose: To investigate the utility of the ultrasmall superparamagnetic iron oxide particles (USPIOs) GEH121333 for measuring tumor response to bevacizumab and compare this with gadolinium‐based DCE‐MRI. Study Type: Prospective preclinical animal model study. ANIMAL MODEL: Mice bearing subcutaneous TOV‐21G human ovarian cancer xenografts treated with bevacizumab (n = 9) or saline (n = 9). Field Strength/Sequence: Imaging was performed on a 7T Bruker Biospec. For SSC‐MRI with GEH121333 we acquired R1 ‐maps (RARE‐sequence with variable TR), R2 ‐maps (multi‐spin echo), and R 2 * ‐maps (multi‐gradient echo). Additionally, R1 and R2 maps were measured on the days after USPIO injection. For DCE‐MRI with gadodiamide we acquired 200 T1 ‐weighted images (RARE‐sequence). Assessment: ΔR1, ΔR2, and Δ R 2 * maps were computed from SSC‐MRI. DCE‐MRI was analysed using the extended Tofts model. Statistical Tests: Results from pre‐ and 3 days posttreatment SSC‐MRI were compared using paired‐sample t‐tests. Treatment and control groups were compared using independent sample t‐tests. Performance of SSC‐ and DCE‐MRI was compared using multivariate partial least squares discriminant analysis. Results: Already one day after treatment and USPIO injection, R1 and R2 values were lower in treated (R1 = 0.49 ± 0.03s −1, R2 = 23.07 ± 1.49s −1 ) compared with control tumors (R1 = 0.52 ± 0.02s −1, R2 = 24.98 ± 1.01s −1 ), indicating lower USPIO accumulation. Posttreatment SSC‐MRI displayed significantly decreased tumor blood volume (change in ΔR2 = ‐0.43 ± 0.26s −1, P = 0.001) and vessel density (change in Q = ‐0.032 ± 0.020s −1/3, P = 0.002). DCE‐MRI showed among others lower K trans in treated tumors (control = 0.064 ± 0.011min −1, tx = 0.046 ± 0.008min −1, P = 0.002). Multivariate analysis suggests that SSC‐MRI was slightly inferior to DCE‐MRI in distinguishing treated from control tumors (accuracy = 75%, P = 0.058 versus 80%, P = 0.028), but a combination of both was best (accuracy = 85%; P = 0.003). Data Conclusion: SSC‐MRI with GEH121333 is sensitive to early (<24 h) and late changes in tumor vasculature. SSC‐MRI and DCE‐MRI provide complementary information and can be used to assess different aspects of vascular responses to anti‐angiogenic therapies. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1589–1600.